Literature review of medication administration problems in paediatrics by parent/caregiver and the role of health literacy - David Terry; Chi Huynh; Dania Talaat Dahmash; Zakia B Shariff; Daniel J Kirby (BMJ Paediatrics Open)
Objective To identify studies that highlighted medication administration problems experienced by parents and children, which also looked at health literacy aspect using a validated tool to assess for literacy.Study design Ten electronic databases were systematically searched and supplemented by hand searching through reference lists using the following search terms: (1) paediatric, (2) medication error including dosing error, medication administration error, medication safety and medication optimisation and (3) health literacy.Results Of the (1230) records screened, 14 studies were eligible for inclusion. Three analytical themes emerged from the synthesis. The review highlighted that frequencies and magnitudes of dosing errors vary by the measurement tools used, the dose prescribed and by the administration instruction provided. Parent’s sociodemographic, such as health literacy and language, is a key factor to be considered when designing an intervention aimed at averting medication administration errors at home. The review summarised some potential strategies that could help in reducing medication administration errors among children at home. Among these recommendations is to show the prescribed dose to the parents or young people along with the verbal instructions, as well as to match the prescribed dose with the measuring tool dispensed, to provide an explicit dose intervals and pictographic dosing instructions.Conclusion The findings suggest that in order to optimise medication use by parents, further work is needed to address the nature of these issues at home. Counselling, medication administration instructions and measurement tools are some of the areas in addition to the sociodemographic characteristics of parents and young people that need to be considered when designing any future potential intervention aimed at reducing medication errors among children and young people at home.